Blind Equalization of Partial Discharge Channels - Žigić, Aleksandar; Kartalovic, Nenad; Radoman, Uros; Kovačevic, Uros (Proceedings, Electrical engineering institute "Nikola Tesla", 2024)
Abstract. In the case of partial discharge signals, obtained during "on-line" monitoring or "off-line" tests of the generator, there is often interference between the direct and reflected signals or disturbances during propagation through the medium, i.e. the structure that transmits the pulse of partial discharges to the measuring terminal or detector. The paper describes the application of the method of "blind equalization" of the partial discharge signal transmission channel, which was shown to be able to be used to extract the direct signal of partial discharges in case of overlap with reflected signals through decorrelation of direct and reflected signals. The term "blind equalization" reflects the ignorance of the characteristics of the channel (transmission medium) and they should be computationally "separated" from the composite signal on the detector.
Keywords: partial discharge, signal analysis, blind equalization, decorrelation, direct signal, reflected signal, superposition